Warfare and the miraculous in the chronicles of the First Crusade - Lapina, Elizabeth, 1979- (The Pennsylvania State University Press, 2015)
"Analyzes how chroniclers of the First Crusade attempted to represent the enterprise as a "holy war." Focuses on accounts of miracles, especially the intervention of saints in the battle of Antioch; explores how the chroniclers related the crusade to biblical events"--Provided by publisher